PRODUKSI PIGMEN OLEH ISOLAT KAPANG HASIL ISOLASI DARI ANGKAK KOMERSIAL DI SEMARANG PADA SUMBER N DAN pH BERBEDA - Soni Nugraha Anwar; Endang Kusdiyantini; Arina Tri Lunggani (Jurnal Akademika Biologi, 2013)
The development of the food processing industry led to the use of dyes have also increased, especially the type of synthetic dyes that can be harmful to consumers because of its toxicity. Natural dyes to be one of the alternatives used in the field of food. One of the natural dyes is widely used as a food coloring that is red yeast rice. Red yeast rice is rice that is overgrown by the mold Monascus sp. that produces pigment. This study aims to obtain pure isolates of red yeast rice molds that are in Semarang and knowing the growth and production of red pigment in the fungi isolates the different source of N and pH. The treatment is done by growing PDB (potato dextrose broth) in the medium with treatment medium pH 3,5,7 and 9 as well as optimization of the nitrogen source Ammonium chloride 1 %, Ammonium Nitrate 1 %, and Peptone 1 %. Analysis of pigments using a spectrophotometer with a wavelength (λ) of 500 nm and analysis of dry cell weight mycelia (g/l). The results showed the highest pigment concentration at treatment pH 7 with 0.812 absorbance value and the highest value of the cell dry weight at pH 7 is 1.232 g/l. Results of optimization with different nitrogen sources showed the highest pigment levels in the addition of a nitrogen source Ammonium Chloride 1 % to the value of 0.821 absorbance and dry weight of most cells are in Ammonium Nitrate is 2.556 g/l. Keywords: Pigment, Angkak, Isolate Fungus, pH, Nitrogen.